Towards Deriving an Optimal Approach for Denoising of RISAT-1 SAR Data Using Wavelet Transform - Ray, Arundhati; Kartikeyan, B; Garg, S (International Journal of Computer Sciences and Engineering, 2025)
Synthetic Aperture Radar(SAR) image filtering has been of interest since its inception. A variety of denoising filters for SAR images have been proposed in the recent years, which are targeted at removing the speckle noise to increase the contrast of the image, and make it useful for further image interpretation and applications. Of late, Wavelet based SAR data denoising techniques have been gaining popularity due to its space-frequency localization capability and the capacity to analyse the data at different scales. In this paper, we have attempted to derive an optimal approach for wavelet based SAR image filtering based on the quality criteria which takes into account not only the radiometric quality but also the geometric quality using point target data of actual Corner Reflector. Different orders of Daubechies wavelet coefficients have been used in the DWT(Discrete Wavelet Transform) based approach. In this study all aspects of an image quality have been taken into consideration such as the geometric fidelity and the radiometric quality, and using a simple heuristic soft thresholding criteria, optimal basis has been arrived at.